Conceptual Dynamism in Terminological Knowledge Bases: The Case of Ecolexicon - Faber, Pamela; León, Pilar (Íkala, Revista de Lenguaje y Cultura, 2010)
The new conceptual-linguistic shift in terminology has given rise to a new approach, focused on discourse and the real use of terms in texts. This change of paradigm has led to a significant improvement in the content of terminological knowledge bases. However, the most innovative aspect of knowledge modeling lies in the wide-ranging use of ontologies. This provides terminology with greater semantic expressiveness. The presentation of the environmental knowledge base, EcoLexicon, developed at the Universidad de Granada, by the research group, EcoLexicon. In order to obtain the maximum benefit from the application of ontologies, a closed inventory of conceptual relations is proposed along with their combinatorial potential. Accordingly, the result is a domain-specific representation, restricted by context. The method is based on data extracted from a corpus of texts compiled for this research, the concepts in the domain are classified according to their typology and relational potential. The characteristics applied are those of the Web Ontology Language (OWL) to make inferences (e.g. the transitivity of metonymy). The definition of conceptual relations, depending on the nature of the concepts, offers a quantitative solution that limits excess information, and at the same time, offers a qualitative solution for knowledge acquisition. EcoLexicon successfully combines terminology with the expressive capacity of ontologies, which in the future will help to define search systems adapted to different user groups.